Transforming into a Platform Provider: Strategic Options for Industrial Smart Service Providers - Beverungen, Daniel; Kundisch, Dennis; Wünderlich, Nancy (Journal of Service Management)
Purpose The purpose of this paper is to identify strategic options and challenges that arise when an industrial firm moves from providing smart service toward providing a platform. Design/methodology/approach This conceptual study takes on a multidisciplinary research perspective that integrates concepts, theories and insights from service management and marketing, information systems and platform economics. Findings The paper outlines three platform types – smart data platform, smart product platform and matching platform – as strategic options for firms that wish to evolve from smart service providers to platform providers. Research limitations/implications Investigating smart service platforms calls for launching interdisciplinary research initiatives. Promising research avenues are outlined to span boundaries that separate different research disciplines today. Practical implications Managing a successful transition from providing smart service toward providing a platform requires making significant investments in IT, platform-related capabilities and skills, as well as implement new approaches toward relationship management and brand-building. Originality/value The findings described in this paper are valuable to researchers in multiple disciplines seeking to develop and to justify theory related to platforms in industrial scenarios.
Keywords: Smart service; Platform; Interdisciplinary research; Manufacturing company; Smart service provider; Platform economics; Information systems; Multi-sided markets; Business-to-business (B2B) markets

How to Build Trust on Peer-to-Peer Platforms: An Investigation of the Antecedents of Peer and Platform Trust - Purrmann, Maren; Wünderlich, Nancy (Proceedings of the 2020 AMA Winter Academic Conference)

Value Co-Creation Patterns in Multi-Actor Service Interactions: A Framework for Collaborative Consumption Platforms - Purrmann, Maren; Wünderlich, Nancy (Proceedings of the 2019 Frontiers in Service Conference)

Overcoming vulnerability: Channel design strategies to alleviate vulnerability perceptions in customer journeys - Wünderlich, Nancy V.; Hogreve, Jens; Chowdhury, Ilma Nur; Fleischer, Hannes; Mousavi, Sahar; Rötzmeier-Keuper, Julia; Sousa, Rui (Journal of Business Research)

Triadic relationships in the context of services for animal companions - Rötzmeier-Keuper, Julia; Hendricks, Jennifer; Wünderlich, Nancy; Schmitz, Gertrud (Journal of Business Research)
Triadic service relationships comprise complex relationships in which not only the customer and provider are involved as partners but also other individuals with caregiving relationships with the customer. A triadic constellation may arise in the context of services for animal companions, for example, when veterinarians provide counsel and treatment to the animal companion and its owner. Through interviews with both owners of animal companions and providers of services for animal companions, this study explores typical constellations and characteristics of the three relationships in this service triad. In line with balance theory, the results show that four distinct types of triadic relationships exist in services for animal companions: the harmonious, the dysfunctional, the challenging, and the doubtful triad. The study highlights the potential conflicts and dynamics in the triads to advise providers on how to address customers depending on the types of triads to which they belong.
Keywords: Triadic relationships; Balance theory; Pet-related services; Animal companions; Service relationship typology; Service triads

Managing Collaborative Consumption Platforms: Successfully Fostering the Co-Creation of Value Between Service Customers and Peer Providers - Purrmann, Maren; Wünderlich, Nancy (Proceedings of the 2018 Frontiers in Service Conference)

How to Handle Dilemmas in Triadic Service Relationships – An Exploratory Study. - Rötzmeier-Keuper, Julia; Wünderlich, Nancy (Proceedings of the 2017 Frontiers in Service Conference)

Renew or cancel? Drivers of customer renewal decisions for IT-based service contracts - Wangenheim, Florian v; Wünderlich, Nancy; Schumann, Jan H (Journal of Business Research)
Manufacturers increasingly integrate information and communication technologies into their products so that they can provide IT-based services. Organizations that formerly concentrated on transactional sales thus confront a new challenge associated with managing service usage—retention and extracting value from investments in smart technology. This study combines a marketing and an information systems perspective in a field study conducted jointly with a large European car manufacturer. Understanding the renewal decision for IT-based service contracts requires knowledge from both disciplines. The paper shows that combining behavioral predictor variables stemming from marketing research and technology-related perceptual variables stemming from technology acceptance research increases the explanatory power and prediction accuracy of forecasting models for customer renewal decisions. Specifically, the authors show that perceptions of usefulness become more important the longer customers use IT-based services and the more services they use within the service contract.
Keywords: IT-based service; Smart services; Contract renewal; Retention; Customer churn; Free trial

“Service Encounter 2.0”: An investigation into the roles of technology, employees and customers - Larivière, Bart; Bowen, David; Andreassen, Tor W; Kunz, Werner; Sirianni, Nancy J; Voss, Chris; Wünderlich, Nancy; De Keyser, Arne (Journal of Business Research)
The service encounter – one of the foundational concepts in service research – is fundamentally changing due to rapid evolutions in technology. In this paper, we offer an updated perspective on what we label the “Service Encounter 2.0”. To this end, we develop a conceptual framework that captures the essence of the Service Encounter 2.0 and provides a synthesis of the changing interdependent roles of technology, employees, and customers. We find that technology either augments or substitutes service employees, and can foster network connections. In turn, employees and customers are taking on the role of enabler, innovator, coordinator and differentiator. In addition, we identify critical areas for future research on this important topic.
Keywords: Service encounter; Technology roles; Employee roles; Customer roles; Employee experience; Customer experience

A Nice and Friendly Chat With a Bot: User Perceptions of AI-Based Service Agents - Wünderlich, Nancy; Paluch, Stefanie (Proceedings of the 38th International Conference on Information Systems (ICIS 2017))

How to Design Successful Gamification in Retail: The benefits and Pitfalls of Affordances - Teßmer, Isabel; Olsson, Marcus; Gustafsson, Anders; Wünderlich, Nancy (Proceedings of the 2017 Frontiers in Service Conference)

Service Encounter 2.0": An Investigation Into the Roles of Technology, Employees and Customers. - Larivière, Bart; Bowen, David; Andreassen, Tor W; Kunz, Werner; Sirianni, Nancy J; Voss, Chris; Wünderlich, Nancy; De Keyser, Arne (Proceedings of QUIS 2017)

Do Companies Really Have to Emphasize the Triple Bottom Line? Analyzing the Effect of Competing Sustainable Market Orientations. - Becker-Özcamlica, Hürrem; Teßmer, Isabel; Wünderlich, Nancy (Proceedings of the 2017 Winter Marketing Educators' Conference)

Reflections on Context in Service Research. - Voss, Chris; Perks, Helen; Sousa, Rui; Witell, Lars; Wünderlich, Nancy (Journal of Service Management)
Purpose – The purpose of this paper is to examine the nature of context and its implications for theory and research in service. Design/methodology/approach – This is a conceptual paper based on exploring existing research and theory related to context in service research. Findings – The characteristics of service make context both important and challenging, there is great contextual diversity in service research as reflected, for example in ecosystems made up of multiple contextual variables. There is a need to identify the context-specific nature of middle range theory and the contextual logic of general theory. The authors explore the challenges of context for service theory and how we might learn from theory in a particular context and test or adapt it in other contexts. Originality/value – The findings of this paper are of value to researchers seeking to develop and justify theory in service research (general, middle range or theory in use).
Keywords: Research; Service theory

Contrasting Risk Perceptions of Technology-Based Service Innovations in Inter-Organizational Settings. - Paluch, Stefanie; Wünderlich, Nancy (Journal of business Research)
Despite the rapid growth and potential of technology-based services, managers' greatest challenges are gaining customer acceptance and increasing usage of these new innovative services. In the B2C field, studies of self-service technology show that perceived risk is an important factor influencing the use of service technology. Though prior research explores different risk types that emerge in consumer settings, risk perception in the B2B setting lacks a detailed examination of different risk types influencing technology-based service adoption. Data from 49 qualitative interviews with providers and customers in two different B2B industries inform this study. The findings emphasize the importance of functional and financial risks in a B2B context and show that business customers' personal and psychological fears hinder their use of technology-based services. Results highlight differences in risk perception and evaluation between customers and providers.
Keywords: Risk perception; Technology-based service innovations; Business-to-business context; Interview study; Risk categories; Smart service

Futurizing” Smart Service: Implications for Service Researchers and Managers. - Wünderlich, Nancy; Heinonen, Kristina; Ostrom, Amy L; Patricio, Lia; Sousa, Rui; Voss, Chris; Lemmink, Jos (Journal of Services Marketing)
Purpose – The purpose of this paper is to craft a future research agenda to advance smart service research and practice. Smart services are delivered to or via intelligent objects that feature awareness and connectivity. For service researchers and managers, one of the most fascinating aspects of smart service provision is that the connected object is able to sense its own condition and its surroundings and thus allows for real-time data collection, continuous communication and interactive feedback. Design/methodology/approach – This article is based on discussions in the workshop on “Fresh perspectives on technology in service” at the International Network of Service Researchers on September 26, 2014 at CTF, Karlstad, Sweden. The paper summarizes the discussion on smart services, adds an extensive literature review, provides examples from business practice and develops a structured approach to new research avenues. Findings – We propose that smart services vary on their individual level of autonomous decision-making, visibility and embeddedness in objects and customer lives. Based on a discussion of these characteristics, we identify research avenues regarding the perception and nature of smart services, the adoption of smart services, the innovation through smart services as well as regarding the development of new business models. Originality/value – Smart services is a new emerging topic in service marketing research, their implications on organizations, customers and the service landscape have not been fully explored. We provide a fresh perspective on service research by characterizing relevant aspects of smart service that will stimulate fruitful future research and advance the understanding and practice of smart services.
Keywords: Connected services; Intelligent object; New service type; Smart services

Conducting Service Research that Matters. - Gustafsson, Anders; Aksoy, Lerzan; Brady, Michael K; McColl-Kennedy, Janet R; Sirianni, Nancy J; Witell, Lars; Wünderlich, Nancy (Journal of Services Marketing)
Purpose – The purpose of this paper is to encourage the reader to think differently about service-related issues and to strive to conduct service research that makes a transformational impact on individuals, organizations and society. The authors suggest that service researchers are in an excellent position to develop research that matters by making stronger connections with theory and elevating purely applied research to research that is higher in both practical relevance and methodological rigor. Design/methodology/approach – This paper takes a conceptual approach, connecting pertinent literature with new ideas highlighted in this special issue. Findings – This paper proposes that service researchers look beyond traditional service applications, take a multi-disciplinary approach to problem-solving and make greater strides towards connecting theory and practice. The authors propose a Model of Rigorous and Relevant Research, and call for fresh thinking across a wide range of research areas, including enhancing the customer experience, crafting innovation, integrating technology and measuring service outcomes. Originality/value – The originality of this essay lies in its focus on revitalizing the discussion on relevance and rigor as a path forward for service research. Additionally, this paper offers new insights on core management aspects of service provision that provide a solid platform for future work in service research.
Keywords: Relevance; Service technology; Service innovation; Customer experience; Rigor; Service outcomes

The Value of Self-Service: Long-Term Effects of Technology-Based Self-Service Usage on Customer Retention. - Scherer, Anne; Wünderlich, Nancy; Von Wangenheim, Florian (MIS Quarterly)
Advancements in information technology have changed the way customers experience a service encounter and their relationship with service providers. Especially technology-based self-service channels have found their way into the 21st century service economy. While research embraces these channels for their cost-efficiency, it has not examined whether a shift from personal to self-service affects customer–firm relationships. Drawing from the service-dominant logic and its central concept of value-in-context, we discuss customers’ value creation in self-service and personal service channels and examine the long-term impact of these channels on customer retention. Using longitudinal customer data, we investigate how the ratio of self-service versus personal service use influences customer defection over time. Our findings suggest that the ratio of self-service to personal service used affects customer defection in a U-shaped manner, with intermediate levels of both self-service and personal service use being associated with the lowest likelihood of defection. We also find that this effect mitigates over time. We conclude that firms should not shift customers toward self-service channels completely, especially not at the beginning of a relationship. Our study underlines the importance of understanding when and how self-service technologies create valuable customer experiences and stresses the notion of actively managing customers’ cocreation of value.
Keywords: customer defection; customer retention; e-service; longitudinal; Self-service; value-in-context

Advancing Research on Loyalty Programs: A Future Research Agenda. - Breugelmans, Els; Bijmolt, Tammo H A; Zhang, Jie; Basso, Leonardo J; Dorotic, Matilda; Kopalle, Praveen; Minnema, Alec; Mijnlieff, Willem Jan; Wünderlich, Nancy (Marketing Letters)
Despite the growing literature on loyalty program (LP) research, many questions remain underexplored. Driven by advancements in information technology, marketing analytics, and consumer interface platforms (e.g., mobile devices), there have been many recent developments in LP practices around the world. They impose new challenges and create exciting opportunities for future LP research. The main objective of this paper is to identify missing links in the literature and to craft a future research agenda to advance LP research and practice. Our discussion focuses on three key areas: (1) LP designs, (2) Assessment of LP performance, and (3) Emerging trends and the impact of new technologies. We highlight several gaps in the literature and outline research opportunities in each area.
Keywords: Loyalty programs; Loyalty program design; Loyalty program performance assessment; Emerging trends; Partnership loyalty programs; Customer relationship management

Customer collectives in healthcare: The transformative potential of service to overcome consumer vulnerability - Rötzmeier-Keuper, Julia; Wünderlich, Nancy (Proceedings of the 39th Annual Macromarketing Conference)

Interdependent Relationships Between and among Service Providers and Customer Collectives. - Rötzmeier-Keuper, Julia; Wünderlich, Nancy (Proceedings of the AMA SERVSIG International Service Research Conference)

Spillover Effects of Service Failures in Coalition Loyalty Programs: The Buffering Effect of Special Treatment Benefits. - Schumann, Jan H; Wünderlich, Nancy; Evanschitzky, Heiner (Journal of Retailing)
Coalition loyalty programs are on the rise, yet few studies investigate the impact of service failures in such programs. Using data from a retail context, the authors show that a program partner deemed responsible for a service failure suffers negative customer responses. However, customers’ perceptions of the benefits of the coalition loyalty program buffer these consequences. Perhaps most importantly, when customers perceive the program's special treatment benefits as low, direct and indirect spillover effects occur, such that a service failure by one program partner has a negative effect on customer loyalty toward the program itself.
Keywords: Service failure; Spillover effects; Buffering effect; Coalition loyalty program

High Tech and High Touch: A Framework for Understanding User Attitudes and Behaviors Related to Smart Interactive Services. - Wünderlich, Nancy; Wangenheim, Florian V; Bitner, Mary Jo (Journal of Service Research)
Smart interactive services, in contrast with other technology-based services, require significant human-to-human interaction and collaboration in addition to the service provided by the embedded technology itself. The authors’ foundational Delphi study confirms smart interactive services (e.g., remote diagnosis, remote repair of equipment, and telemedicine) are a rapidly growing innovation category across industries. Yet, gaining user acceptance of these types of services presents a significant challenge for managers. To address this challenge, the authors employ a grounded theory approach, drawing on depth interviews, to develop a framework of barriers and facilitators to users’ attitudinal and behavioral responses to smart interactive services. The findings reveal a new set of beliefs that are critical in this context. These beliefs are tied to the human element and specifically pertain to beliefs about the “service counterpart (SC),” who is the provider’s employee controlling the technology. Control, trustworthiness, and collaboration beliefs emerge jointly as important and interrelated influencers tied to the SC. Contrary to conventional wisdom that focuses on features of the technology itself to gain user acceptance, this research encourages providers to emphasize the interpersonal elements of the service by providing control cues, raising social presence, and enhancing human trust mechanisms.
Keywords: service technology; technology-mediated service; service counterpart; smart service; remote service; technology adoption

Perils of Managing the Service Profit Chain: The Role of Time Lags and Feedback Loops. - Evanschitzky, Heiner; Wangenheim, Florian v; Wünderlich, Nancy (Journal of Retailing)
The tendency of managers to focus on short-term results rather than on sustained company success is of particular importance to retail marketing managers, because marketing activities involve expenditures which may only pay off in the longer term. To address the issue of myopic management, our study shows how the complexity of the service profit chain (SPC) can cause managers to make suboptimal decisions. Hence, our paper departs from past research by recognizing that understanding the temporal interplay between operational investments, employee satisfaction, customer satisfaction, and operating profit is essential to achieving sustained success. In particular, we intend to improve understanding of the functioning of the SPC with respect to time lags and feedback loops. Results of our large-scale longitudinal study set in a multi-outlet retail chain reveal time-lag effects between operational investments and employee satisfaction, as well as between customer satisfaction and performance. These findings, along with evidence of a negative interaction effect of employee satisfaction on the relationship between current performance and future investments, show the substantial risk of mismanaging the SPC. We identify specific situations in which the dynamic approach leads to superior marketing investment decisions, when compared to the conventional static view of the SCP. These insights provide valuable managerial guidance for effectively managing the SPC over time.
Keywords: Employee satisfaction; Customer satisfaction; Performance; Service profit chain; Feedback loops; Time lags; Myopic marketing management

Culture’s Impact on Customer Motivation to Engage in Professional Service Enactments. - Schumann, Jan H; Wünderlich, Nancy; Zimmer, Marcus S (Schmalenbach Business Review)
Although professional service providers increasingly deliver their services globally, little is known about cross-cultural differences in customers’ motivation to participate in service production. To address this lacuna, we survey a total of 2,284 banking customers in 11 countries on their motivation to provide personal information to, and follow the advice of, their service providers. We find differences in both aspects, but only the differences in providing personal information can be explained by the cultural values of uncertainty avoidance, individualism/collectivism, and masculinity/femininity. To perform certain tasks in the service process, global professional service providers should acknowledge cultural differences in customers’ motivations.
Keywords: Co-Production; Culture; Customer Participation; Professional Services

Technology Mediation in Service Delivery: A New Typology and an Agenda for Managers and Academics. - Schumann, Jan H; Wünderlich, Nancy; Wangenheim, Florian (Technovation)
The role of information and communication technology for economic growth has been emphasized repeatedly. Technological breakthroughs have generated new forms of services, such as self-services or remote services. Although these encounters are qualitatively different from traditional service provision, prior service management literature thus far had paid little attention to theory development and the systematization of technology-based service encounters. To fill this research gap, the present study outlines how new types of technology-based services fit into existing service typologies and provides an extension of existing frameworks to capture their unique characteristics. These insights in turn offer managerial implications and highlight open research questions.
Keywords: Services; Remote services; Self-services; Technology mediation

Management und Marketing ferngesteuerter Dienstleistungen: Konzeptionelle Verortung, betriebswirtschaftliche Herausforderungen und künftige Forschungsaufgaben. - Wünderlich, Nancy; Schumann, Jan H; Wangenheim, Florian v; Holzmüller, Hartmut H (Zeitschrift für Betriebswirtschaft)
Die Möglichkeiten der Erbringung von Dienstleistungen haben sich durch die Entwicklungen der Informations- und Kommunikationstechnologien stark erweitert. Unter Zuhilfenahme moderner Formen der Datenfernübertragung kann eine breite Palette von Dienstleistungen technologisch vermittelt über große Entfernungen hinweg erbracht werden. Diesen als ferngesteuerte Dienstleistungen bezeichneten Angeboten kommt in der Praxis eine immer größere Bedeutung zu. In der betriebswirtschaftlichen Literatur wurde ihnen bisher jedoch wenig Beachtung geschenkt. In diesem Überblicksartikel erfolgt daher eine erste Auseinandersetzung mit betriebswirtschaftlich relevanten Aspekten ferngesteuerter Dienstleistungen. Ausgehend von einer begrifflichen Abgrenzung und Konzeptualisierung dieses neuen Dienstleistungstypus im Abgleich mit bestehenden Systematisierungsansätzen werden die spezifischen Herausforderungen des Management und Marketing von ferngesteuerten Dienstleistungen reflektiert und sowie künftige Forschungsaufgaben abgeleitet.
Keywords: Technologieintensive Dienstleistungen; remote services; Dienstleistungstechnologien

Geschäftsmodelle in virtuellen Spielwelten

Acceptance of Remote Services – Perception, Adoption, and Continued Usage in Organizational Settings - Wünderlich, Nancy
The increasing employment of information and communication technologies in companies and households has led to considerable changes in the way services are conceived, developed, and delivered. Nancy V. Wünderlich employs a multi-method approach comprising an international qualitative study in Germany, USA and China and a longitudinal quantitative study to analyze remote services. She develops the Interactive Technology-Mediated Service Model (ITSUM) to provide a comprehensive approach of explaining both initial acceptance and repeated, continued usage of remote services in organizations. Finally, she derives managerial implications for remote service providers on how to increase remote service acceptance among their customers and facilitate the export of remote services.